Paradigma Ahl Al-Sunnah Wa Al-Jama'ah dan Signifikansinya dalam Pendidikan Islam Multikultural - Fikri, Ishom Fuadi; Fahrurrozi, Imam; Habibi, Adib Habibi (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2022)
The discourse of Ahl al-Sunnah wa al-Jama'ah (Aswaja) in the Nahdlatul Ulama (NU) tradition has developed in a paradigmatic framework as the manhaj al-fikr (the method of thinking) to answer the challenges of heterogeneity in the Indonesian nation. This paper is a literature review using a descriptive-deductive approach in answering questions about how the Aswaja concept is a paradigmatic proposition in the midst of the plurality in the Indonesian nation and how significant it is in enriching the insight of multiculturalism in Islamic education. In this case, Aswaja as the manhaj al-fikr is a continuation of the madzhab diniyyah system (religious school) which stems from five main foundations, i.e. tawassut (moderate), tasammuh (tolerant), tawazun (balanced), ‘adalah (justice), and amar ma’ruf nahi munkar (encouraging good deeds and preventing evil deeds). In addition, Aswaja as the manhaj al-fikr contributes to multicultural Islamic education by providing a paradigmatic scheme as a weltanschauung or worldview in seeing and responding to all the diversity that exists in Indonesia. That is, performing Aswaja in a manhajiy manner means an ability to; 1) manage conflicts proportionally, 2) live side by side peacefully in the midst of differences, 3) seek improvement towards a better direction (al-ishlah ila ma huwa al-ashlah), 4) contextualize in responding to various problems, and 5) think methodologically. Thus, the Aswaja paradigm as the manhaj al-fikr has significance in enriching the concept of Islamic education with a multicultural perspective in the internalization aspect of religious moderating and strengthening national integration.